Protective effect of dried fruits of Carica papaya on hepatotoxicity in rat (Bangladesh Journal of Pharmacology, 2010)
Aqueous and ethanol extracts of Carica papaya has been evaluated for its hepatoprotective activity in rats. The aqueous and ethanol extracts of C. papaya showed significant hepatoprotection against carbon tetrachloride induced hepatotoxicity. The protective activity was evaluated by using biochemical parameters such as serum bilirubin, serum alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase. The histopathological changes of liver were compared with control.